Quadrastichus mendeli (Hymenoptera: Eulophidae) parasitizing Leptocybe invasa (Hymenoptera: Eulophidae) on Eucalyptus spp. Seedlings. - Mota, T A [UNESP]; Teixeira, D L; Souza, A R; Passos, J R [UNESP]; Puretz, B O [UNESP]; Dallacort, S [UNESP]; Souza, C D [UNESP]; Serrão, J E; Zanuncio, J C; Wilcken, C F [UNESP] (FapUNIFESP (SciELO), 2025)
Galls by Leptocybe invasa Fisher & La Salle (Hymenoptera: Eulophidae) reduce the productivity of Eucalyptus spp. plantations and Quadrastichus mendeli Kim & La Salle (Hymenoptera: Eulophidae) parasitizes this pest. This study aimed to evaluate, under laboratory conditions, two biological control strategies against Leptocybe invasa using the parasitoid Quadrastichus mendeli: (i) inundative biological control (referred to here as applied biological control), consisting of the release of five mated females per seedling, and (ii) natural biological control, representing the action of naturally occurring populations of the parasitoid already established in the environment. Ninety-day-old seedlings of the clone 3025 (Eucalyptus grandis × E. camaldulensis), naturally infested by L. invasa, were placed individually in cages under controlled conditions (25 ± 2 °C; 70 ± 10% RH; 12 h photoperiod) in a completely randomized design with 22 replicates per treatment. The number of insects was adjusted using zero-inflated mixed nonlinear regression models. The emergence of L. invasa adults (p>0.05) was similar between treatments, but that of Q. mendeli greater with the release of five females of this natural enemy per seedling compared to the applied biological control. The controlled release of Q. mendeli reduced L. invasa damage on Eucalyptus seedlings, increasing the importance of applied biological control to manage this pest in cultivated forests.